Estudio comparativo de la clase esqueletal según Ricketts y MC namara en radiografías cefalométricas de un consultorio privado de Iquitos, 2023 - Lazarte Rengifo, Arnold Leskov (2024)
The objective of this study was to establish the difference between the skeletal class according to Ricketts and McNamara in cephalometric radiographs from a private practice. The study is quantitative. The design will be non-experimental, cross-sectional, and correlational. The population will consist of 80 cephalometric radiographs of patients treated in a private practice (OrthoEstetic). 78.75% of the sample was female and 21.25% were male. 32.5% were class I according to both analyses; 17.5% were class II, and 6.3% were class III. 15% were class II according to Ricketts and class I according to McNamara; 12.5% were class I according to Ricketts and class II according to McNamara; 6.3% were class III according to Ricketts and class I according to McNamara, and 10% were class I according to Ricketts and class III according to McNamara. The skeletal class of Ricketts and McNamara is similar. (p = 0.000)